Heterocyclic amines and polycyclic aromatic hydrocarbons in commercial ready-to-eat meat products on UK market. (March 2017) - Lu, Fei; Kuhnle, Gunter K.; Cheng, Qiaofen
Abstract: Heterocyclic amines (HCAs) and polycyclic aromatic hydrocarbons (PAHs), which are developed during meat processing, may play key roles in the imposing health risk. The consumption of ready to eat (RTE) meat products has increased dramatically in recent years due to their convenience. Therefore, it is essential to evaluate its health risk and provide dietary intake guidance to the general public. 11 RTE meat products were selected from UK market including chicken, pork and fish to investigate their health risks in concern of HCAs and PAHs levels. HCAs and PAHs were extracted by solid-phase extraction and analysed by HPLC-DAD/FLU. Chargrilled chicken contained the highest amount of HCAs (37.45 ± 4.89 ng/g) and PAHs (3.11 ± 0.49 ng/g), followed by roasted bacon (HCAs 15.24 ± 1.31 ng/g, PAHs 1.75 ± 0.17 ng/g) and honey roast salmon (HCAs 17.12 ± 5.86 ng/g, PAHs 0.38 ± 0.09 ng/g). The high dietary intake of HCAs was from chargrilled chicken and ham, which could contribute to the increase in breast cancer and colorectal adenoma. While cancer risk associated with PAHs intake from RTE meat products was relatively low according to the Lifelong Average Daily Intake of UK consumers. Highlights: Chargrilled chicken contained the highest amount of HCAs and PAHs. Increasing dietary intake of HCAs from chargrilled chicken and ham might elevate the health risk. Cancer risk associated with PAHs intake from RTE meat products was relatively low.